Transformational Leadership, Motivation, and Work Stress in Improving Police Performance - Kentut Lintang Tenggono; Hakim, Lukmanul; M. Hasan Ma'ruf (ITB AAS Indonesia Surakarta, 2025)
The performance of personnel in police organizations is a crucial aspect that determines the quality of public services and the effectiveness of the institution. Leadership factors, work motivation, and psychological conditions such as work stress are important determinants that affect the achievement of optimal performance. This study aims to analyze the influence of transformational leadership and work motivation on the performance of Lampung Police Biddokkes personnel, as well as test the role of work stress as a moderation variable. The research method uses a quantitative approach with a causal associative design. The research population is all Biddokkes personnel as many as 104 people, who were made respondents through saturated sample techniques. The data was collected using a Likert scale questionnaire and tested by validity, reliability, classical assumptions, and path analysis. The results showed that transformational leadership had a significant positive effect on performance, as well as work motivation. Simultaneously, both affect performance with strong significance values. In addition, work stress has been shown to moderate the relationship with an increase in the coefficient of determination. These findings confirm that transformational leadership and work motivation are able to improve performance, but their effectiveness is greatly influenced by stress levels. Research recommendations include individual attention-based leadership training, a fair reward system, and integrated work stress management strategies to support the optimization of police personnel performance. Keywords: Transformational Leadership, Work Motivation, Work Stress, Performance